Analisis Kinerja Perbankan Syariah di Indonesia dengan Pendekatan Maqashid Indeks - Suhada Suhada; Pramono Sigit (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2014)
Maqoshid index is one of the alternatives in measuring the performance of Islamicbanking, Islamic banking which assessed aspects attainment of goals sharia. In thisresearch the author tried to assess the performance of Islamic banking in Indonesiawith maqoshid index approach. This research uses descriptive quantitativemethodology to the entire study population of Islamic banking in Indonesia, while thesample is that Islamic banking has published an annual report 3 year. This researchusing purposive sampling method. From the results of the research with maqoshidindex approach, in 2009 and 2010 BMI become Islamic bank which the bestperformance with best ratio value are 13.67% and 13,64 whereas in 2011 BSMbecame the best performance Islamic Bank with the best value ratio of 13.85%.